Volunteers' Demographics That Affect the Human-Dog Interaction During Walks in a Shelter - Shih, Hao-Yu; Paterson, Mandy B. A.; Pachana, Nancy A.; Phillips, Clive J. C. (Frontiers in Veterinary Science, 2021)
Different people relate to dogs in different ways. We investigated differences between volunteers in their behavioural interactions with shelter dogs when they were walked on a leash. Cameras were used to record and quantify the behaviour of volunteers and a leash tension meter was used to measure pulling by both volunteers and shelter dogs. Effects of volunteers’ age, body height, educational level, marital status, and experiences of living and working with dogs, and living with children, were examined. Older volunteers talked to the dogs more often during the walk than younger ones. Taller volunteers had reduced physical contact with dogs, and dogs pulled more frequently on the leash while walking with them. Volunteers with a postgraduate degree more frequently praised dogs and rewarded dogs with food and used more body language in the form of hand gestures and physical contact. Married and partnered volunteers more often praised dogs, while separated/divorced or widowed volunteers initiated more frequent physical contacts. Dogs pulled less when walking with volunteers who had experience of living with dogs, and these volunteers interacted with dogs using fewer verbal and body languages. Finally, those living with children more frequently communicated with dogs using body language (e.g. hand gestures and physical contact). We conclude that shelters should carefully consider volunteers’ demographics when selecting them to walk dogs with various behavioural characteristics.